Penerapan Problem-Based Learning Melalui Eksperimen Filter Air Sederhana untuk Menumbuhkan Kesadaran Lingkungan Siswa Kelas V SDN 184 Pekanbaru - Adinda Febriza; Nazwa Nursakinah; Neni Hermita; Rifqa Gusmida Syahrun Barokah (STKIP HARAPAN BIMA, 2026)
This study aims to foster students’ environmental awareness, particularly regarding the clean water crisis, through the application of a Problem-Based Learning (PBL) model based on an experiment to construct a simple water filter. The study employs a qualitative descriptive approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 42 fifth-grade students at SDN 184 Pekanbaru. The research procedure was carried out through the stages of needs analysis, instructional design, development of PBL-based teaching materials, implementation of group-based experimental activities, and evaluation of learning outcomes. Data collection was conducted through observation, cognitive tests, and documentation of activities, then analyzed descriptively to describe students’ achievements in scientific understanding and the development of their environmental awareness. In the experiment, students were divided into five groups to design and build water filters using natural materials such as activated charcoal, sand, cotton, and gravel. The results showed that the group that placed activated charcoal as the first layer produced the clearest and most odorless water, proving that the order of the materials significantly affects filtration quality. In the cognitive test, 55% of students received a “Good” grade and 45% received a “Satisfactory” grade. This study concluded that the application of PBL through contextual experiments effectively fosters students’ environmental awareness, while also encouraging the development of scientific curiosity, critical thinking skills, teamwork, and a sense of responsibility for environmental sustainability.